Control and manipulation of cold atoms in optical tweezers - Muldoon, C; Brandt, L; Dong, J; Stuart, D; Brainis, E; Himsworth, M; Kuhn, A (Deutsche Physikalische Gesellschaft, 2012)
Neutral atoms trapped by laser light are among the most promising candidates for storing and processing information in a quantum computer or simulator. The application certainly calls for a scalable and flexible scheme for addressing and manipulating the atoms. We have now made this a reality by implementing a fast and versatile method to dynamically control the position of neutral atoms trapped in optical tweezers. The tweezers result from a spatial light modulator (SLM) controlling and shaping a large number of optical dipole-force traps. Trapped atoms adapt to any change in the potential landscape, such that one can rearrange and randomly access individual sites within atom-trap arrays. © IOP Publishing Ltd and Deutsche Physikalische Gesellschaft.